Association of organisational factors with work-related musculoskeletal disorders and psychological well-being: a job demand control model study - Singh P.; Bhardwaj P.; Sharma S.K.; Agrawal A.K. (My University, 2025)
Musculoskeletal disorders (MSDs) are a major work-related problem affecting employees’ well-being worldwide. Employee well-being is also associated with high organisational financial and social costs. Most working adults spend a considerable amount of time at their workplace, thus making workplace conditions a critical factor affecting their physical and mental health. This study addresses the role of work-related factors on WMSDs and psychological stress. For this purpose, 210 managers working in middle-level management in an Indian telecom organisation participated in the study. Data for the study was collected using a self-reported questionnaire. 64% of employees reported WMSDs, and 60% psychological stress. Structural equation modelling was used to study the effect of work-related factors on WMSDs and psychological stress. The study reported neck and lower back pain being the most frequently reported WMSD. Job control had a significant negative effect on WMSDs, and psychological stress, while workload did not affect either. Age was significantly associated with pain in the upper back and knees. The results suggested that increasing job control will result in employees’ better physical and psychological well-being. © 2022 Informa UK Limited, trading as Taylor & Francis Group.